Growing and changing : a handbook for pre-teens - McCoy, Kathy 1945-; Wibbelsman, Charles; Stover, Bob (New York : Perigee Books, 1986)
Addresses questions pre-teens have about puberty in such areas as body changes, changes in feelings, hygiene, health problems, and talking to doctors and parents.
Includes index.
Keywords: Sex instruction for children; Puberty -- Juvenile literature